Design, analysis & fabrication of a scaled down model of an open channel flow flume and weir - Mohd Firdaus, Mohd Rosli (2013)
Thin plate weirs have been widely used for measuring discharge rate in open channel flow accurately. The flow characteristic over a thin plate weir is completely different between a single V notch weir and double VV notch weir. The continuity of the flow and accuracy of this type of weirs is reported to be poor. As an improvement, a compound weir composed of two triangle parts with a different notch angle and height has been designed. Mathematical method also been proposed to measure the discharge flow rate over the double VV notch compound weir. Height and width of weir plate are the two parameters characterizing discharge rate over the notch weirs. Mathematical calculation and simulation are conducted by measuring the discharge and the height over the weir for variable weir height and width.